REKONSTRUKSI CITRA CT DENGAN METODE BACK PROJECTION (BP) DAN ALGEBRAIC RECONSTRUCTION TECHNIQUE (ART) MENGGUNAKAN MATLAB - Ariyanti Nur Anisa; Evi Setiawati; Choirul Anam (Youngster Physics Journal, 2012)
Have been made CT image reconstruction with Back Projection method (BP) and Algebraic Recontruction Technique (ART) used Matlab. Image reconstruction used parallel beam in the projection angle from 0 to 180 degree, with interval 5, 7,5 and 10 degrees. In this research, the number pixels was 30x30. The result shows us that image reconstruction used BP method  still there are lots of blurring, while the image reconstruction used  ART method can display the same object with the original image. In the smaller interval of the angle projections, then it will get better results, but it takes longer. Keywords: image reconstruction, parallel beam, back projection, algebraic reconstruction technique